Long term exposure to ambient fine particulate matter and incidence of stroke: prospective cohort study from the China-PAR project. (30th December 2019) - Huang, Keyong; Liang, Fengchao; Yang, Xueli; Liu, Fangchao; Li, Jianxin; Xiao, Qingyang; Chen, Jichun; Liu, Xiaoqing; Cao, Jie; Shen, Chong; Yu, Ling; Lu, Fanghong; et al.
Abstract: Objective: To study the effect of long term exposure to ambient fine particulate matter of diameter ≤2.5 μm (PM2.5 ) on the incidence of total, ischemic, and hemorrhagic stroke among Chinese adults. Design: Population based prospective cohort study. Setting: Prediction for Atherosclerotic Cardiovascular Disease Risk in China (China-PAR) project carried out in 15 provinces across China. Participants: 117 575 Chinese men and women without stroke at baseline in the China-PAR project. Main outcome measures: Incidence of total, ischemic, and hemorrhagic stroke. Results: The long term average PM2.5 level from 2000 to 2015 at participants' residential addresses was 64.9 μg/m 3, ranging from 31.2 μg/m 3 to 97.0 μg/m 3 . During 900 214 person years of follow-up, 3540 cases of incident stroke were identified, of which 63.0% (n=2230) were ischemic and 27.5% (n=973) were hemorrhagic. Compared with the first quarter of exposure to PM2.5 (<54.5 μg/m 3 ), participants in the highest quarter (>78.2 μg/m 3 ) had an increased risk of incident stroke (hazard ratio 1.53, 95% confidence interval 1.34 to 1.74), ischemic stroke (1.82, 1.55 to 2.14), and hemorrhagic stroke (1.50, 1.16 to 1.93). For each increase of 10 μg/m 3 in PM2.5 concentration, the increased risks of incident stroke, ischemic stroke, and hemorrhagic stroke were 13% (1.13, 1.09 to 1.17), 20% (1.20, 1.15 to 1.25), and 12% (1.12, 1.05 to 1.20), respectively. Almost linear exposure-response relations between long term exposure to PM2.5 and incident stroke, overall and by its subtypes, were observed. Conclusions: This study provides evidence from China that long term exposure to ambient PM2.5 at relatively high concentrations is positively associated with incident stroke and its major subtypes. These findings are meaningful for both environmental and health policy development related to air pollution and stroke prevention, not only in China, but also in other low and middle income countries.